Pengaruh Non Performing Loan, Net Interest Margin, Beban Operasional Berbanding Pendapatan Operasional dan Fee Based Income terhadap Laba Perusahaan (Studi Kasus Pada Bank Pembangunan Daerah Di Indonesia Periode 2015-2020) - Muhammad Rusdiansyah; Hayat, Atma; Hamdani (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study examines the influence of (1) the relationship between Non-Performing Loan on company profits, (2) the relationship between Net Interest Margin on company profits, (3) the relationship between Operating Expenses Compared to Operating Income on company profits, and (4) the relationship between Fee-Based Income on company profits at Local Development Bank in Indonesia. The population in this study were all Local Development Banks in Indonesia, numbering 26 banks, while the sampling technique used was Saturation Sampling. The method of collecting secondary data is based on the annual report of the Local Development Bank in Indonesia with an observation period of 2015-2020. Data analysis techniques used are multiple regression analysis with double-log regression model and SPSS. The analysis found that Non-Performing Loan, Net Interest Margin, Operating Expenses Compared to Operating Income and Fee-Based Income affect company profits.